A framework of best practices for improving maintenance management for building facility (case study: UiTM Seri Iskandar) / Mohamad Hilman Hazim Mohamed Ariffin and Alia Abdullah Saleh - Mohamed Ariffin, Mohamad Hilman Hazim; Abdullah Saleh, Alia (2023)
A building exists to serve the user’ s space requirement. The essence of maintenance is, therefore, to maximize the service life of a building, by delaying deterioration, decay, and failure. Building maintenance management is a complex and multi-faceted thought process that involves planning, directing, controlling, and organizing resources for the sustenance of the building’ s functional performance. The purpose of this paper is to propose an alternative maintenance management model for university buildings. Although this research is specifically proposed for university buildings, however, many public and private sector institutions face similar maintenance management problems. Therefore, this research has broader applications. This research emerged from the need for an alternative building maintenance management system that reflects current thinking on the efficient and effective use of maintenance resources. This research used a quantitative research method that included survey distribution and collection. The 15 questions about best practices for improving maintenance management for building facility were created as surveys and separated into three sections. Data was collected with high confidence from a sample size of 50 respondents. The implementation of best practices to improve maintenance management statistics was assessed using the IBM SPSS Statistics software version 28. According to the survey results, the majority of respondents who in-house and outsource in maintenance department believe that there are various more methods that may be implemented to improve maintenance management in Univerisiti Teknologi MARA (UiTM) Seri Iskandar.